Bioactive polymeric formulations for wound healing - Nada, Ahmed A. (Polym Adv Technol, 2018)
Ricinoleic acid (RA) has potential to promote wound healing because of its analgesic and anti-inflammatory properties. This study investigates the synthesis and characterization of RA liposomes infused in a hydrogel for topical application. Lecithin liposomes containing RA were prepared and incorporated into a chitosan solution and were subsequently cross-linked with dialdehyde β-cyclodextrin (Di-β-CD). Chitosan/Di-β-CD concentrations and reaction temperatures were varied to alter gelation time, water content, and mechanical properties of the hydrogel in an effort to obtain a wide range of RA release profiles. Hydrogel cross-linking was confirmed by spectroscopy, and liposome and carrier hydrogel morphology via microscopy. Chitosan, Di-β-CD, and liposome concentrations within the formulation affected the extent of matrix swelling, mechanical strength, and pore and overall morphology. Higher cross-linking density of the hydrogel led to lower water uptake and slower release rate of RA. Optimized formulations resulted in a burst release of RA followed by a steady release pattern accounting for 80% of the encapsulated RA over a period of 48 hours. However, RA concentrations above 0.1 mg/mL were found to be cytotoxic to fibroblast cultures in vitro because of the oily nature of RA. These formulations promoted wound healing when used to treat full thickness skin wounds (2 cm(2)) in Wister male rats. The wound contraction rates were significantly higher compared to a commercially available topical cream after a time period of 21 days. Histopathological analysis of the RA-liposomal chitosan hydrogel group showed that the epidermis, dermis, and subcutaneous skin layers displayed an accelerated yet normal healing compared to control group.